Comparative Analysis of Resilience and Life Values Among Muslim Higher Education Students: The Influence of Traumatic Experiences, Gender, and Living Area - Bahrun Bahrun; Nurbaity Bustamam; Abu Bakar; Hetti Zuliani; Dara Rosita; Saminan Saminan; Amiruddin Amiruddin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2023)
This study wanted to see how resilience and life values might be different in Muslim college students based on their past experiences with trauma, their gender, and whether they live in a city or the countryside. We asked students from Aceh, Indonesia, to take part in our study. This area has seen a lot of trauma from a big tsunami and a civil war. We used two tools, the Brief Resilience Scale and the Life Values Inventory, to measure resilience and life values. Our results showed that students who had experienced trauma were more resilient. But we didn't find any differences in resilience or life values based on gender or where the students lived. We did find that students who were more resilient also had stronger life values. This tells us that we need to think about past trauma and life values when we're trying to understand resilience in Muslim college students. In the future, we need to keep studying these things and come up with ways to help these students be more resilient and have strong life values.